Gegen Qinlian Decoction treatment of asymptomatic hyperuricemia by targeting circadian immune function - Xiaojun Wang; Xuanqi Liu; Qiushuang Gao; Xuchao Gu; Guannan Zhang; Zhiyuan Sheng; Tao Wu; Zheling Su; Wenhao Wang; Maoqing Ye (BMC, 2023)
Abstract Background The Gegen Qinlian Decoction (GGQLD) is a renowned traditional Chinese medicinal formula that has been used for centuries to effectively treat asymptomatic Hyperuricemia (HUA). This study aims to investigate the underlying mechanism of GGQLD's therapeutic effects on HUA. Methods The study enrolled a total of 25 healthy participants and 32 middle-aged and elderly individuals with asymptomatic HUA. All asymptomatic HUA participants were treated with GGQLD. Venous blood samples were collected from all participants to isolate peripheral blood mononuclear cells (PBMCs), which were then analyzed for biological profiles using flow cytometry. Network pharmacology analysis was utilized to identify the potential pathways involved in the therapeutic effects of GGQLD. Transcriptomic patterns of cultured proximal tubule epithelial cells (PTECs) were evaluated via bulk RNA-seq, and critical differentially expressed genes (DEGs) were identified and verified through ELISA. Molecular docking and molecular dynamics (MD) simulation were employed to investigate the potential compounds in GGQLD that may be involved in treating HUA. Results Network pharmacology analysis revealed that immune-related pathways might be involved in the therapeutic mechanism of GGQLD. RNA-seq analysis confirmed the involvement of innate lymphoid cell (ILC) development-related genes and clock genes. Polychromatic flow cytometric analysis demonstrated that GGQLD treatment reduced the proportion of ILC3s in total ILCs in asymptomatic HUA patients. ELISA results showed that GGQLD treatment reduced the levels of activating factors, such as ILC3-IL-18 and IL-1β, in the plasma of HUA patients. GGQLD was also found to regulate circadian clock gene expression in PBMCs to treat asymptomatic HUA. Furthermore, the interaction between 40 compounds in GGQLD and HDAC3 (Histone Deacetylase 3), NLRP3 (NOD-like receptor protein 3), RORA (RAR-related orphan receptor A), and REV-ERBα (nuclear receptor subfamily 1) revealed that GGQLD may regulate ILCs and clock genes to treat asymptomatic HUA. Conclusions The regulation of circadian clock gene expression and the proportion of ILC cells may be involved in the therapeutic effects of GGQLD on asymptomatic HUA patients.